2013
DOI: 10.1016/j.econmod.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Is the relationship between monetary policy and house prices asymmetric across bull and bear markets in South Africa? Evidence from a Markov-switching vector autoregressive model

Abstract: Abstract. This paper examines asymmetries in the impact of monetary policy on the middle segment of the South African housing market from 1966:M2 to 2011:M12. We use Markov-switching vector autoregressive (MS-VAR) model in which parameters change according to the phase of the housing cycle. The results suggest that monetary policy is not neutral as house price growth decreases substantially with a contractionary monetary policy. We find that the impact of monetary policy is larger in bear regime than in bull r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…2011;Ncube and Ndou 2011;Aye, Gupta, and Modise 2012;Peretti, Gupta, and Inglesi-Lotz 2012;and Simo-Kengne, Gupta, and Bittencourt forthcoming). Also, the timevarying approaches of Aye, Gupta, and Modise (2012) and Peretti, Gupta, and Inglesi-Lotz (2012) show that the South African economy began slowing by the end of 2007, as the stock and housing markets entered deep bear markets (Venter 2011 andSimo-Kengne et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2011;Ncube and Ndou 2011;Aye, Gupta, and Modise 2012;Peretti, Gupta, and Inglesi-Lotz 2012;and Simo-Kengne, Gupta, and Bittencourt forthcoming). Also, the timevarying approaches of Aye, Gupta, and Modise (2012) and Peretti, Gupta, and Inglesi-Lotz (2012) show that the South African economy began slowing by the end of 2007, as the stock and housing markets entered deep bear markets (Venter 2011 andSimo-Kengne et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Switching regressions are models allowing the estimated parameters to change depending on the realization of one among many unobservable states. This approach developed by Golfeld and Quandt (1973) is now commonly used for the estimation of asymmetries in economic patterns (Simo-Kengne et al 2013). In this paper, it is assumed that throughout period from January 1982 to February 2019, US crude oil production switches between two unobservable states: bull market corresponding to high oil production and bear market corresponding to low oil production.…”
Section: Markov-switching Modelmentioning
confidence: 99%
“…Regarding the interdependence between monetary policy and house price movements, many studies have found that monetary policy significantly affects house prices, especially when it is too liberal. Indeed, house price booms are typically preceded by periods of loose monetary policy (Dokko et al (2011);Seyfried (2010); Ahearne et al (2008); Simo-Kengne et al (2013); Taylor (2007); Greiber and Setzer (2007); Jarocinski and Smets (2008); Antipa and Lecat (2009); Escobari et al (2013)). Monetary policy can affect house prices through several channels.…”
Section: Literature Reviewmentioning
confidence: 99%